Foreign body reaction against cellophane in the athymic nude mice - Smetana, K; Holub, M; Slavcev, A (Journal of biomedical materials research, 1989)
There are no differences in the multinucleate cell formation in normal and athymic mice after the subcutaneous implantation of a cellophane strip. The number of Ia+ epitheloid cells and multinucleate foreign body giant cells was lower and the number of epitheloid cells sharing the marker of activated macrophages (M 57) was higher in athymic compared to normal mice. The epitheloid cells of athymic and euthymic animals exhibited no difference in the expression of Mac-2 molecule. The difference of the expression of surface markers between athymic and euthymic animals does not influence the foreign body giant cell formation.
Keywords: implantované léky; myši; Drug Implants; reakce na cizí těleso; Mice, Nude; Cellophane; zvířata; Mice; Foreign-Body Reaction; celofán; Skin; myši nahé; kůže; Animals